Consequences of social media marketing on the brand equity of leading mobile telephone operators in South Africa - Mathabatha, Marole (My University, 2017)
Whilst the marketing literature on social media marketing in Africa has grown over the past few years, not much has been written about the consequences of social media marketing on the brand equity of leading mobile telephone operators. To address this gap, this research conducted a qualitative study using reports and interviews with social media marketing practitioners from MTN and Vodacom, where the purpose was to investigate evidence of the intended and unintended consequences of social media marketing on brand equity of leading South African mobile telephone service providers. By means of an open code system, the average 45 minutes interviews’ data was collected, transcribed and analysed. Reports were collected from companies, newspapers, social media analysts and commentators. These findings show that social media marketing has had positive consequences on brand loyalty as it allowed companies to form strong long-term relationships through daily interactions. Moreover, MTN and Vodacom’s ability to form brand communities on social media has added value to their brand equity. Furthermore, the findings suggest that the consequences of social media are largely intended. Unintended consequences, although limited, were found to be the client’s ability to communicate service dissatisfaction in a manner that negatively influences perceptions of other people on the brand. The study will assist marketing practitioners in marketing plans implementation to avoid unintended harm on brand equity, social media strategies’ design and effective integration of social media in the marketing mix to enhance brand equity. Further implications for this study are that it will encourage practitioners to motivate the establishment of social media brand communities, thus enhancing brand equity. Although the consequences of social media can impact on other elements, the study is limited to an impact on brand equity of telecommunications companies in South Africa. Using a quantitative research method, customer perspective and a larger sample, future studies can look at the extent to which social media marketing influences customer purchase intentions.
MBA
Keywords: Social media -- Economic aspects. Brand name products. Branding (Marketing) -- South Africa.